Mechanical properties of iron doped bismuth microwires in glass isolation - Dîntu, Maria (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2009)
The mechanical properties of iron doped bismuth microwires by the breaking and flexing test methods were studied and the structural defect morphology, in combination with chemical reagent attack, was analyzed. The analysis of experimental data permits us to conclude that iron forms microscopic inclusions in the bismuth matrix, leading to the breaking strength increase and the flexing strength diminution in comparison with the microwires of pure bismuth.